Clinical decision support for gastrointestinal panel testing - Nadia T. Saif; Cara Dooley; Jonathan D. Baghdadi; Daniel J. Morgan; KC Coffey (Cambridge University Press, 2024)
Abstract Objective: This study aimed to assess the impact of clinical decision support (CDS) to improve ordering of multiplex gastrointestinal polymerase chain reaction (PCR) testing panel ("GI panel"). Design: Single-center, retrospective, before-after study. Setting: Tertiary care Veteran's Affairs (VA) Medical Center provides inpatient, outpatient, and residential care. Patients: All patients tested with a GI panel between June 22, 2022 and April 20, 2023. Intervention: We designed a CDS questionnaire in the electronic medical record (EMR) to guide appropriate ordering of the GI panel. A "soft stop" reminder at the point of ordering prompted providers to confirm five appropriateness criteria: 1) documented diarrhea, 2) no recent receipt of laxatives, 3) C. difficile is not the leading suspected cause of diarrhea, 4) time period since a prior test is >14 days or prior positive test is >4 weeks and 5) duration of hospitalization <72 hours. The CDS was implemented in November 2022. Results: Compared to the pre-implementation period (n = 136), fewer tests were performed post-implementation (n = 92) with an IRR of 0.61 (p = 0.003). Inappropriate ordering based on laxative use or undocumented diarrhea decreased (IRR 0.37, p = 0.012 and IRR 0.25, p = 0.08, respectively). However, overall inappropriate ordering and outcome measures did not significantly differ before and after the intervention. Conclusions: Implementation of CDS in the EMR decreased testing and inappropriate ordering based on use of laxatives or undocumented diarrhea. However, inappropriate ordering of tests overall remained high post-intervention, signaling the need for continued diagnostic stewardship efforts.